2020
DOI: 10.1038/s41388-020-01495-6
|View full text |Cite
|
Sign up to set email alerts
|

SUV39H1 regulates the progression of MLL-AF9-induced acute myeloid leukemia

Abstract: Epigenetic regulations play crucial roles in leukemogenesis and leukemia progression. SUV39H1 is the dominant H3K9 methyltransferase in the hematopoietic system, and its expression declines with aging. However, the role of SUV39H1 via its-mediated repressive modification H3K9me3 in leukemogenesis/leukemia progression remains to be explored. We found that SUV39H1 was down-regulated in a variety of leukemias, including MLL-r AML, as compared with normal individuals. Decreased levels of Suv39h1 expression and gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…In recent years, an increasing number of studies have found that drugs targeting TFs can modulate some hallmark properties of cancer. For example, MLL-AF9 is a driver of the leukemia stem cell population (7); GABP increases expression of TERT in glioblastomas with a mutant TERT promoter (8); PML-RARa blocks cell differentiation in acute promyelocytic leukemia (9); RUNX1-ETO reduces CD48, thereby decreasing NK cell killing (10); Runx2 and SIX1 induce epithelial-mesenchymal transition (EMT) and breast cell invasion (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, an increasing number of studies have found that drugs targeting TFs can modulate some hallmark properties of cancer. For example, MLL-AF9 is a driver of the leukemia stem cell population (7); GABP increases expression of TERT in glioblastomas with a mutant TERT promoter (8); PML-RARa blocks cell differentiation in acute promyelocytic leukemia (9); RUNX1-ETO reduces CD48, thereby decreasing NK cell killing (10); Runx2 and SIX1 induce epithelial-mesenchymal transition (EMT) and breast cell invasion (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Suppressor of variegation 3–9 homolog 1 (SUV39H1), the first characterized mammalian domain-containing histone methyltransferase, catalyzes tri-methylation of histone 3 lysine 9 (H3K9me3) [ 87 ]. It is generally reported to be a tumor suppressor.…”
Section: Regulation Of Ferroptosis In Renal Carcinomamentioning
confidence: 99%
“…Several lines of evidence documented a tumor suppressive role of SUV39H1 through its stabilization and silencing of heterochromatin. It has been found that SUV39H-deficient mice develop B-cell lymphomas with increased frequencies [ 54 ], and SUV39H1 was observed to be downregulated in many leukemias [ 82 ]. The protective effect of SUV39H1 in leukemia was validated in mouse models using SUV39H1 overexpression or knockdown and the data provided a direct link between SUV39H1 and AML via the silencing of HOXB13 and SIC1 [ 82 ].…”
Section: Biological Roles Of Suv39h1 and Suv39h2mentioning
confidence: 99%
“…It has been found that SUV39H-deficient mice develop B-cell lymphomas with increased frequencies [ 54 ], and SUV39H1 was observed to be downregulated in many leukemias [ 82 ]. The protective effect of SUV39H1 in leukemia was validated in mouse models using SUV39H1 overexpression or knockdown and the data provided a direct link between SUV39H1 and AML via the silencing of HOXB13 and SIC1 [ 82 ]. Similarly, tumorigenesis driven by Ras or Myc is accelerated by the loss of SUV39H1 [ 83 , 84 ].…”
Section: Biological Roles Of Suv39h1 and Suv39h2mentioning
confidence: 99%